Island protected area zoning based on ecological importance and tenacity. (May 2020) - Chi, Yuan; Zhang, Zhiwei; Wang, Jing; Xie, Zuolun; Gao, Jianhua
Highlights: Ecological importance and tenacity were proposed to represent the specialty of islands. Two new indices, EII and ETI, were used to quantify the importance and tenacity, respectively. The combination of EII and ETI provided an effective method to conduct island protected area zoning. The optimum scheme of island protected area zoning could be obtained using the method. Targeted island protected area zoning greatly contributes to the island sustainable development. Abstract: Island protected area zoning is highly significant for maintaining the biodiversity and achieving the island sustainable development. Ecological importance and tenacity were proposed in this study for the island protected area zoning. The ecological importance was composed of three components, namely, landscape, soil, and vegetation; the ecological tenacity was evaluated based on the ecological importance and considering three types of influences, i.e., anthropogenic, topographic, and marine influences. Two new indices, namely, ecological importance index (EII) and ecological tenacity index (ETI), were established, and remote sensing and field data were integrated to serve as the data source and realize the spatial exhibitions. Then, the island protected area zoning was conducted based on the spatial distributions of EII and ETI, and six schemes for different protection and development purposes were designed. An island chain in Dongtou Archipelago in South China was used as the study area. Results indicated that the ecological importance and tenacity showed spatial heterogeneities across islands and within the islands. The islands with higher proximities to the mainland and larger areas generally possessed lower ecological importance and tenacity. Of the six schemes, Scheme B was the recommended scheme because of its reasonable area assignments for different protected areas, the optimum compatibility with island uses, and the balance of protection and development. The demonstration of the method validated the advantages of the EII and ETI in revealing the spatial characteristics of island ecological importance and tenacity, as well as the effectiveness of the method in the island protected area zoning.